Advances in Discourse Analysis - Suciu, Lavinia (IntechOpen, 2019)
This book is an open access publication edited by IntechOpen. Its main goal is to summarize current research in the discourse analysis area. It provides a scientific platform for researchers to publish the latest studies and developments in both theoretical and practical aspects of discourse analysis and to make it more visible. The book is an excellent way for disseminating inspiring visions, innovative research methods, and research findings in this interdisciplinary field.It is a fact that in our postmodern times, the discourse has gained new connections and dimensions through fundamental changes and structural progress. Therefore, the research of the discourse generates new knowledge, creates a favorable atmosphere for change, and provides people with information and data that help them to benefit directly in their everyday life.